Chitosan-Based Nanoparticles Against Viral Infections - Boroumand, Homa; Badie, Fereshteh; Mazaheri, Samaneh; Seyedi, Zeynab Sadat; Nahand, Javid Sadri; Nejati, Majid; Baghi, Hossein Bannazadeh; Abbasi-Kolli, Mohammad; Badehnoosh, Bita; Ghandali, Maryam; Hamblin, Michael R.; Mirzaei, Hamed (Frontiers in Cellular and Infection Microbiology, 2021)
Viral infections, in addition to damaging host cells, can compromise the host immune system, leading to frequent relapse or long-term persistence. Viruses have the capacity to destroy the host cell while liberating their own RNA or DNA in order to replicate within additional host cells. The viral life cycle makes it challenging to develop anti-viral drugs. Nanotechnology-based approaches have been suggested to deal effectively with viral diseases, and overcome some limitations of anti-viral drugs. Nanotechnology has enabled scientists to overcome the challenges of solubility and toxicity of anti-viral drugs, and can enhance their selectivity towards viruses and virally infected cells, while preserving healthy host cells. Chitosan is a naturally occurring polymer that has been used to construct nanoparticles (NPs), which are biocompatible, biodegradable, less toxic, easy to prepare, and can function as effective drug delivery systems (DDSs). Furthermore, chitosan is Generally Recognized as Safe (GRAS) by the US Food and Drug Administration (U.S. FDA). Chitosan NPs have been used in drug delivery by the oral, ocular, pulmonary, nasal, mucosal, buccal, or vaginal routes. They have also been studied for gene delivery, vaccine delivery, and advanced cancer therapy. Multiple lines of evidence suggest that chitosan NPs could be used as new therapeutic tools against viral infections. In this review we summarize reports concerning the therapeutic potential of chitosan NPs against various viral infections.